Cloning and Characterization of Limonoid Glucosyltransferase from Kinnow Mandarin (Citrus reticulata Blanco) - Sumedha Arora; Prashant Mohanpuria; Gurupkar Singh Sidhu; Inderjit Singh Yadav; Vandna Kumari (Food Technology and Biotechnology, 2018)
Kinnow mandarin (Citrus reticulata Blanco) is a popular citrus crop of northwestern India and it occupies maximum fruit area in Punjab. However, citrus juice processing industry is still suffering from delayed bitterness problem caused mainly by limonoid aglycones such as limonin. In order to study citrus limonoid metabolism, limonoid glucosyltransferase (LGT) gene, which encodes a natural debittering enzyme, was isolated from the fruit tissues of Kinnow mandarin. After confirmation and characterization, its full-length gene sequence (1533 bp) was submitted to National Centre for Biotechnology Information. Citrus reticulata limonoid glucosyltransferase (CrLGT) occupies a position on an independent branch in the largest subgroup and is phylogenetically different from those in other mandarin species like C. unshiu, showing its uniqueness in several features. The transcript expression of CrLGT, evaluated in different tissues such as young leaf, flavedo, albedo, sac covering and seed of Kinnow mandarin during early (90 days after flowering (DAF)), mid (150-210 DAF) and late (240 DAF) fruit developmental stages using semi-quantitative method, showed the highest expression in flavedo. Thus, it was concluded that the isolated LGT gene has an effect on limonoid metabolic engineering in citrus. Overexpression of this gene can reduce the delayed bitterness problem in citrus juice and enhance the accumulation of specific glucosides that have anticancer effects.